An Overview of OSH Management Systems in the Water Service Project - Mohamed Younos, Mohamad Mahathir; Fathi, Mohamad Syazli (Journal of Advanced Research in Business and Management Studies, 2020)
Construction delay is a common situation in every construction project. Delay happens in all construction projects, whether it is a simple or a complex project. When the projects are delayed, they will invite to the additional cost. Therefore, managing project delay is important. The aim of this project is to examine the management of the delayed completion on construction projects and the objectives of this study are to evaluate the degree of delay on construction projects, to identify the notification of delay on construction projects and to investigate the respondent’s actions when rectifying the delayed completion. To achieve these objectives, questionnaire surveys were distributed to thirty respondents. The result of the study shows that the more complex project, the less likely it is to complete on time, therefore, more liabilities (Extension of Time and compensation) have been imposed for complex projects. The study also reveals that the delay is only identified when the schedule is updated and reissued while by working overtime, it is said that it was the most preferred action to be taken to rectify the delay.